2012
DOI: 10.1061/(asce)hy.1943-7900.0000540
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Simulation of Wave-Induced Tunnel Scour beneath Marine Pipelines

Abstract: An Eulerian two-phase flow model was presented and employed to investigate waveinduced tunnel scour beneath a marine pipelines. The model is based on the Euler-Euler coupled governing equations for the fluid and sediment phases, i.e. time-averaged continuity and momentum equations were solved for both phases with a modified k-ε turbulence closure for the fluid phase. Fluid-particle, particle-particle and fluid-structure interactions were implemented in the simulation. The model accounts for the interphase mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The earliest attempts to model scour beneath pipelines were made using potential flow models, whereas more recent attempts were carried out by solving the complete Navier-Stokes equations, either in the form of the Reynolds-averaged Navier-Stokes equations (RANS), or using Large Eddy Simulation (LES). Brørs (1999), Liang and Cheng (2005b), Liang et al (2005) Zhao and Fernando (2007), and Zanganeh et al (2012) succeeded in modelling the scour evolution beneath pipelines in steady currents and Liang and Cheng (2005a), Kazeminezhad et al (2012) and Fuhrman et al (2014) modelled the scour beneath a pipeline due to waves. Fuhrman et al (2014) demonstrated accurate scour time scales, while also managing to simulate the backfilling process caused by a change to milder wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest attempts to model scour beneath pipelines were made using potential flow models, whereas more recent attempts were carried out by solving the complete Navier-Stokes equations, either in the form of the Reynolds-averaged Navier-Stokes equations (RANS), or using Large Eddy Simulation (LES). Brørs (1999), Liang and Cheng (2005b), Liang et al (2005) Zhao and Fernando (2007), and Zanganeh et al (2012) succeeded in modelling the scour evolution beneath pipelines in steady currents and Liang and Cheng (2005a), Kazeminezhad et al (2012) and Fuhrman et al (2014) modelled the scour beneath a pipeline due to waves. Fuhrman et al (2014) demonstrated accurate scour time scales, while also managing to simulate the backfilling process caused by a change to milder wave conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the pore pressure responses to the current and waves were considerably different in different types of soil due to the variation in the properties of the soils. Kazeminezhad et al (2012) presented an Eulerian two-phase flow model for the waveinduced scour beneath the pipeline and observed the tremendous sediment transport in the high turbulence intensity after the onset of scour.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental studies carried out by Sumer and Fredsøe [2], Fredsøe et al [6], Cheng et al [7] and Qi and Gao [8], the scour process under waves at different KCs was also investigated using a stochastic method by Myrhaug et al [9] and numerical simulations by Liang and Cheng [10], Kazeminezhad et al [11], Fuhrman et al [3] and Li et al [12]. The main challenge in numerical simulations of the scour process is how to resolve the interactions among the flow, the sediments, and the structures.…”
Section: Introductionmentioning
confidence: 99%